Cesarean delivery in Nigeria: Prevalence and associated factors •a population-based cross-sectional study - Adewuyi, Emmanuel; Auta, A.; Khanal, V.; Tapshak, S.J.; Zhao, Yun (BMJ PUBLISHING GROUP, 2019)
Objective To investigate the prevalence and factors associated with caesarean delivery in Nigeria. Design This is a secondary analysis of the nationally representative 2013 Nigeria Demographic and Health Survey (NDHS) data. We carried out frequency tabulation, χ 2 test, simple logistic regression and multivariable binary logistic regression analyses to achieve the study objective. Setting Nigeria. Participants A total of 31 171 most recent live deliveries for women aged 15-49 years (mother-child pair) in the 5 years preceding the 2013 NDHS was included in this study. Outcome measure Caesarean mode of delivery. Results The prevalence of caesarean section (CS) was 2.1% (95% CI 1.8 to 2.3) in Nigeria. At the region level, the South-West had the highest prevalence of 4.7%. Factors associated with increased odds of CS were urban residence (adjusted OR (AOR): 1.51, 95% CI 1.15 to 1.97), maternal age ≥35 years (AOR: 2.12, 95% CI 1.08 to 4.11), large birth size (AOR: 1.39, 95% CI 1.10 to 1.74) and multiple births (AOR: 4.96, 95% CI 2.84 to 8.62). Greater odds of CS were equally associated with maternal obesity (AOR: 3.16, 95% CI 2.30 to 4.32), Christianity (AOR: 2.06, 95% CI 1.58 to 2.68), birth order of one (AOR: 3.86, 95% CI 2.66 to 5.56), husband's secondary/higher education level (AOR: 2.07, 95% CI 1.29 to 3.33), health insurance coverage (AOR: 2.01, 95% CI 1.37 to 2.95) and ≥4 antenatal visits (AOR: 2.84, 95% CI 1.56 to 5.17). Conclusions The prevalence of CS was low, indicating unmet needs in the use of caesarean delivery in Nigeria. Rural-urban, regional and socioeconomic differences were observed, suggesting inequitable access to the obstetric surgery. Intervention efforts need to prioritise women living in rural areas, the North-East and the North-West regions, as well as women of the Islamic faith.